The Effect of Financial Literacy and Self-Control on Students' Consumptive Behavior: English - Sri Darmawati, Lusi Endang; Ruski, Ruski; Jannah, Raudatul; Jailani, Ahmad (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
Consumptive behavior is a negative thing that needs to be avoided, especially in students or students. Therefore, good financial literacy and self-control are needed. In this study, the author aims to determine the effect of financial literacy and self-control on students' consumptive behavior. The research method used is quantitative method. Data collection techniques are carried out by distributing questionnaires, observations and documentation. Data analysis techniques are carried out by testing the validity and reliability of instruments, classical assumption tests and hypothesis tests with t tests and f tests. The results of this study show that financial literacy has a partial effect on students' consumptive behavior. Furthermore, self-control has a partial effect on students' consumptive behavior. And at the same time, financial literacy and self-control have a significant effect on students' consumptive behavior. Thus, students who have good financial literacy and self-control will be better able to control consumptive behavior that has a negative impact.